Squared diffusion-weighted imaging for improving the detection of clinically significant prostate cancer - Birte Valentin; Lars Schimmöller; Matthias Boschheidgen; Tim Ullrich; Thomas Andreas Thiel; Alexandra Ljimani; Jan Philipp Radtke; Thomas Benkert; Peter Albers; Gerald Antoch; Hans-Jörg Wittsack; Michael Quentin (Scientific Reports)
Abstract Aim of this study was to proof the concept of optimizing the contrast between prostate cancer (PC) and healthy tissue by DWI post-processing using a quadrature method. DWI post-processing was performed on 30 patients (median age 67 years, prostate specific antigen 8.0 ng/ml) with PC and clear MRI findings (PI-RADS 4 and 5). Multiparametric MRI was performed at 3 Tesla. A multi-shot readout segmentation (rs-EPI) plus zoomed single-shot imaging (z-EPI) sequence was used in 15 patients (group 1) and a single-shot echo-planar imaging (ss-EPI) plus rs-EPI sequence in 15 patients (group 2). B-value images (b1000 and b1800/2000) were squared and then evaluated objectively software-based and subjectively using a 5-point. The squared DWI technique showed a significantly higher contrast ratio (CR) for ss-EPI b1800 (p < 0.001), rs-EPI b1000 (p < 0.001), rs-EPI b1800 (p < 0.001), z-EPI b1000 (p = 0.008) and for z-EPI b2000 (p < 0.001). After post-processing, a significant improvement in the subjective assessment of image quality was observed for rs-EPI b1000 (p < 0.001), rs-EPI b1800 (p < 0.001) and z-EPI b1000 (p < 0.001). The application of the square post-processing to DWI results in a significant improvement in the CR between PC and healthy tissue, especially at high b-values of ss-EPI or re-EPI. This method may help to improve the detection and differentiation of PC lesions.